2020
DOI: 10.1021/acsomega.0c04390
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of a Recombinant Exolytic GH50A β-Agarase from Cellvibrio sp. KY-GH-1 for Enzymatic Production of Neoagarobiose from Agarose

Abstract: Neoagarobiose (NA2) is the repeating disaccharide unit of agarose and possesses various promising biological activities. To identify an efficient exolytic βagarase required for NA2 production from agarose, the GH50A β-agarase gene from agar-degrading Cellvibrio sp. KY-GH-1 was overexpressed as a recombinant Histagged protein using the Escherichia coli expression system. GH50A β-agarase that consists of 797 amino acids was able to produce predominantly NA2 from agarose at an optimal temperature and pH of 35 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…A standard NAOS mixture (NA2–NA18) was provided by Dr. Sang-Hyeon Lee (Lee et al 2008 ). An AOS mixture was prepared by mild acid hydrolysis of 1%[w/v] agarose as previously described (Kwon et al 2020 ). The standards (NA2, NA4, and NA6) were obtained from Carbosynth Ltd. (Berkshire, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard NAOS mixture (NA2–NA18) was provided by Dr. Sang-Hyeon Lee (Lee et al 2008 ). An AOS mixture was prepared by mild acid hydrolysis of 1%[w/v] agarose as previously described (Kwon et al 2020 ). The standards (NA2, NA4, and NA6) were obtained from Carbosynth Ltd. (Berkshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Endo-acting β-agarases from the GH16, GH86, and GH118 families degrade agarose into neoagarotetraose (NA4) and neoagarohexaose (NA6), NA6 and neoagarooctaose (NA8), and NA8 and neoagarodecaose (NA10), respectively. The β-agarase members of GH50 family degrade agarose via exo-acting activity or a combination of exo- and endo-acting activities to produce neoagarobiose (NA2) (Kwon et al 2020 ; Han et al 2016 ), NA4 (Chen et al 2018 ), or NA2 and NA4 (Li et al 2015 ; Liang et al 2017 ) as end products. GH96 α-agarases hydrolyze agarose into agarotetraose (Flament et al 2007 ; Lee et al 2019 ), whereas GH117 α-neoagarobiose hydrolases (α-NABH) cleave NA2 into L-AHG and D-Gal (Ha et al 2011 ; Jang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In detail, 10 μL enzyme solution was mixed with 240 μL agarose (0.4%; w / v ) with different pHs including 3.0–8.0 (50 mM sodium citrate-dibasic sodium phosphate), 8.0–9.0 (50 mM Tris-HCl), and 9.0–10.6 (50 mM glycine-NaOH), and the mixture was incubated at the temperatures of 0, 10, 20, 30, 35, 40, 45, 50, 60, 70, and 80 °C for 10 min, respectively. Then, 750 μL 3,5-dinitrosalicylic acid (DNS) solution was added, and the resulting sugar was measured by the DNS method [ 28 ]. To determine the stability against pH, rAgaW1540 was pre-incubated in the above-mentioned pH buffers at 25 °C for 60 min, and then the residual activity was determined.…”
Section: Methodsmentioning
confidence: 99%
“…11 These activities are likely related to the presence of AHG and DP in the structure. 12,13 In fact, oligosaccharides prepared from agarose have a wide range of applications in the pharmaceutical, food, and cosmetic industries. 14,15 However, the intestinal transport study of NAOS and AOS with different DP in vitro has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize and quantify, a procedure for simultaneous determination of NAOS and AOS with different DP was required. Currently, a variety of analytical methods for components of NAOS and AOS have been published, including HPLC-ELSD, 12 MALDI-TOF/MS, 22,23 HPAEC-PAD, 24,25 LC-MS/MS, 13 and LC/MS-IT-TOF 26 (Table 1). However, most of them were qualitative analysis used for the separation and purication of crude products.…”
Section: Introductionmentioning
confidence: 99%